In vitro rooting of Crocosmia × crocosmiiflora ‘Lucifer’ - Krupa-Małkiewicz Marcelina; Żurawik Piotr (Folia Horticulturae, 2017)
The aim of this study was to determine the effect of various auxins and their concentrations on Crocosmia × crocosmiiflora ‘Lucifer’ rooting in in vitro cultures and in vivo conditions. The initial research materials were shoots obtained from a stabilized in vitro culture. MS media were supplemented with the following auxins: IAA, IBA and NAA at concentrations of 0.5, 1.0, 2.0 and 5.0 mg dm-3. The results of the study showed that hormone applications had a positive effect on the root development of Crocosmia microshoots. 100% rooted shoots were observed in each of the applied combinations of the experiment. The highest number of roots and the longest roots were formed in the presence of IBA at a concentration of 1.0 mg dm-3. IAA, IBA and NAA affected plant height and root morphology of Crocosmia differently. The addition of higher concentrations of auxins to the medium (2.0 and 5.0 mg dm-3) resulted in the formation of short roots. The applied IBA concentrations determined the percentage of the plants that were adapted to in vivo conditions, as well as their vegetative features and the yield of descendant tubers. At the end of the vegetation period, higher IBA concentrations, i.e., 1.0, 2.0 and 5.0 mg dm-3, caused a decrease of up to 50-75% in the obtained plants and also inhibited plant height, as well as the weight and diameter of the tubers formed, compared to the control.